The Relationship between Risk Factors for the Use of Oral Contraception and Sexual Activity with Cervical Cancer Incidence at Dr. M Djamil General Hospital, Padang, Indonesia - Hidayat, Ahmad; Syifa (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Cervical cancer is a malignancy of the cervix caused by the human papilloma virus (HPV). Cervical cancer often has no symptoms. Most patients are known to be positive for cervical cancer at an advanced stage. This study aim ed to determine the relationship between the use of oral contraceptives a nd sexual activity with the incidence of cervical cancer at Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: This study was an analytic observational case-control study. A total of 37 subjects were researched as a case group and a total of 111 subjects as a control group. This study made observations of variable age, Education, work, use of oral contraceptives, and sexual activity for the first time. Data analysis was carried out using SPSS software univariate and bivariate. Results: Use of oral contracepti ves ≥ 5 years was not significantly associated with the incidence of cervical cancer, p> 0.05. Age at first sexual intercourse <18 years was signif icantly associated with the incidence of cervical cancer, p<0.05. Age at first pregnancy <18 years was significantly associated with the incidence of cervical cancer, p<0.05. Conclusion: Sexual activity is a risk factor that plays a role in the incidence of cervical cancer at Dr. M Djamil General Hospital, Padang, Indonesia.